Risk factors for atopic eczema in school children Fatores de risco para eczema atópico em escolares - Gustavo F. Wandalsen; Inês C. Camelo-Nunes; Karyn C. Mello; Charles K. Naspitz; Dirceu Solé (Instituto Materno Infantil de Pernambuco, 2005)
OBJECTIVES: to study risk factors related to atopic eczema (AE) in school children of São Paulo. METHODS: 1972 parents or guardians of 6-7 years old children in the Southern Central area of São Paulo answered to a written questionnaire (standardized questionnaire of the International Study of Asthma and Allergies in Childhood plus a complementary questionnaire regarding family history of asthma and allergies, and exposure to environmental allergens). AE was defined by the presence of an itchy rash in the last year. Risk factors were analyzed through logical regression. RESULTS: the following factors were significantly associated with AE: history of maternal (OR: 4.1; 95%CI: 2.4 to 7.1) and paternal eczema (OR: 2.6; 95%CI: 1.4 to 5.0), dust in the child's bedroom (OR: 1.6; 95%CI: 1.1 to 2.4), lower maternal education (OR: 1.7; 95%CI: 1.1 to 2.7), rhinitis fever (OR: 1.7; 95%CI: 1.1 to 2.9) and wheezing in the last year (OR: 1.9; 95%CI: 1.2 to 2.8). CONCLUSIONS: our data suggest that AE has a specific pattern of inheritance. The presence of dust in the child's bedroom was the single environmental risk factor found. Diagnose of other allergic diseases, as well as the presence of recent symptoms were strongly associated with AE in children. OBJETIVOS: identificar fatores de risco relacionados ao eczema atópico (EA) em escolares do município de São Paulo. MÉTODOS: 1972 pais de escolares de 6-7 anos da região centro-sul de São Paulo responderam a questionários escritos (questionário padrão do International Study of Asthma and Allergies in Childhood e questionário complementar sobre história familiar de doenças alérgicas e exposição ambiental a potenciais fontes de alérgenos e irritantes). A presença de manchas na pele com coceira nos últimos 12 meses, definiu os escolares com EA. Os fatores de risco foram analisados por regressão logística. RESULTADOS: as variáveis significantemente associadas ao EA foram: história materna (OR: 4,1; IC95%: 2,4 a 7,1) e paterna de eczema (OR: 2,6; IC95%: 1,4 a 5,0), presença de pó no dormitório (OR: 1,6; IC95%: 1,1 a 2,4), menor escolaridade materna (OR: 1,7; IC95%: 1,1 a 2,7), relato de sibilos no último ano (OR: 1,9; IC95%: 1,2 a 2,8) e de rinite alguma vez (OR: 1,7; IC95%: 1,1 a 2,9). CONCLUSÕES: a análise dos dados sugeriu haver um padrão específico de herança genética para o EA. A presença de pó no quarto foi o único fator de risco ambiental encontrado. Sintomas e diagnóstico de outras doenças atópicas associaram-se fortemente às manifestações de EA.